Turbinas eólicas: evolução da análise aerodinâmica e desafios encontrados - Queiroz, Eduardo Henrique Moreira de (2021)
Horizontal-axis wind turbines (HAWTs) are the most common type of wind power generation, since these turbines have been of great importance to decrease the environmental impacts generated by the use of fossil fuels, since the increasing participation of wind energy in the global energy matrix. With the constant technological advances, HAWTs have had their dimensions increased, requiring models that can predict more performance characteristics including effects such as fluid-structure interaction, turbulent wake and yawed winds. This paper provides an overview of wind turbine theory and the challenges in the analysis of HAWTs in order to improve the knowledge of wind turbines in the aerodynamic domain, since more reliable models are needed that can capture important phenomena such as fluid-structure interaction, aeroelastic effects, and turbulent wake. Recent studies that aim to include such phenomena in their analysis have been taken into consideration, so that the technology becomes more and more accessible, fostering the creation of new jobs and diversifying the energy matrix of the region that allows the use of such technology.